Genetically Engineered Mouse Models Support a Major Role of Immune Checkpoint-Dependent Immunosurveillance Escape in B-Cell Lymphomas - Lemasson, Quentin; Akil, Hussein; Feuillard, Jean; Vincent-Fabert, Christelle (Frontiers in Immunology, 2021)
These last 20 years, research on immune tumor microenvironment led to identify some critical recurrent mechanisms used in cancer to escape immune response. Through immune checkpoints, which are cell surface molecules involved in the immune system control, it is now established that tumor cells are able to shutdown the immune response. Due to the complexity and heterogeneity of Non Hodgkin B-cell Lymphomas (NHBLs), it is difficult to understand the precise mechanisms of immune escape and to explain the mitigated effect of immune checkpoints blockade for their treatment. Because genetically engineered mouse models are very reliable tools to improve our understanding of molecular mechanisms involved in B cell transformation and, at the same time, can be useful preclinical models to predict immune response, we reviewed hereafter some of these models that highlight the immune escape mechanisms of NHBLs and open perspectives on future therapies.